Impact of Compensation on Employee Motivation in the Telecommunication Industry in Azerbaijan - Muradzada, Elvin (My University, 2020)
In the highly competitive telecommunication industry, managing human resources has become one of the principal strategies and tools to improve competitive advantage and to maintain the existence and growth of the relevant companies, as the availability of competent and motivated employees enable the business companies to generate expected employee performance and boost their production capacity. In this regard, the compensation of employees is regarded as one of the principal means for managing the employees and improving their productivity and activities. Accordingly, a data networking and telecommunication corporations, the subsidiary of Nokia Solutions and Networks in Azerbaijan, Delta Telecom and Azer Telecom also need to manage their human resources for preserving their market position in the telecommunication industry in Azerbaijan. Hence, the study aimed to demonstrate whether the remuneration is an effective tool in boosting employee motivation in the selected telecommunication companies operating in Azerbaijan. The review of previous studies revealed that there is a positive connection between employee motivation and compensation. The existing researches highlight that the employee motivation, including their commitment, willingness, their lack of absenteeism and turnover is positively influenced by the various forms of compensation, including financial and non-financial modes of remuneration. Furthermore, in this research, the different motivation theories were reviewed for explaining why employees tend to be motivated in the workplace when they are given the fair compensation. The study was undertaken as an explanatory research in telecommunication industry via quantitative data gathered through questionnaires, as the study aims to explain whether monetary and nonmonetary payments influence on the motivation of employees in chosen telecommunication companies in Azerbaijan. Hence, the target population of this research was the sum of full-time staff members working for one of the selected companies, which was 148 employees. Furthermore, the research sample consisted of 67 full-time employees, including technical and administrative staff members working for one of the chosen companies. The regression analysis was adopted to analyze the gathered quantitative. The regression analysis of primary data found out that in the selected telecommunication companies in Azerbaijan, the employee motivation is positively influenced by the different compensation packages, including salary, bonus, promotion, and employee recognition. Furthermore, the research demonstrated that the sick leave payments restrict the employee motivation to be present in the workplace because this compensation method gives an incentive for employees of the selected telecommunication companies to miss the work for attaining financial benefit.
Keywords: Business; Employee motivation -- Azerbaijan.; Remuneration methods.; Employee absenteeism -- Azerbaijan.; Employee turnover -- Azerbaijan.; Telecommunication industry -- Azerbaijan.